The Sociodemographic Characteristics of Incest Cases in the Evaluation of Bulent Ecevit University Hospital - Yılmaz, Rıza; Eryılmaz, Ahmet (The Bulletin of Legal Medicine, 2016)
Objective: Incest is defined as sexual activity between people with close blood ties including family members and kinship who are prohibited by law. There are few studies in Turkey about incest which is a kind of child sexual abuse. In order to understand the characteristics of incest in Zonguldak, cases who are sent to BEU (Bulent Ecevit University) Hospital of Medical Faculty by courts or prosecution offices were evaluated as socio-demographic.Materials and Methods: The cases were sent to the polyclinic of Forensic Medicine of the Hospital in order to be given reports between July 2010 and June 2014.  The cases were investigated retrospectively with regards to age, gender, education level, abuse type, the level of intelligence, the findings of psychiatric examinations and the degree of kinship with attacker.Results: The cases among 3-38 years of ages consist of a total of 39 cases, 38 female and 1 male. When patients are examined in terms of education, 10 of them under 7 years did not start school due to their smallness ages. Despite older ages of 2 persons they were not sent to any school at all. After primary school, 6 cases did not continue any school.Conclusion: Incest which is concerned by all the community regarding health, education, social, economic and political aspect and needed a multidisciplinary approach for the solution. Cases of incest can be minimized or can be eliminated by taking precautions within a plan in where regional and all over the country to be pre- pared for short, medium and long term.
Keywords: incest; child abuse; sexual abuse; domestic violence; forensic medicine